Integrated Analysis of mRNA and MicroRNA Co-expressed Network for the Differentiation of Bovine Skeletal Muscle Cells After Polyphenol Resveratrol Treatment - Hao, Dan; Wang, Xiao; Yang, Yu; Thomsen, Bo; Holm, Lars-Erik; Qu, Kaixing; Huang, Bizhi; Chen, Hong (Frontiers in Veterinary Science, 2021)
Resveratrol (RSV) has been confirmed to benefit human health. RSV supplemented in the feeds of animals improved pork, chicken and duck meat qualities. In this study, we identified differentially expressed (DE) mRNAs (n = 3,856) and microRNAs (miRNAs) (n = 93) for the weighted correlation network analysis (WGCNA) to investigate the co-expressed DE mRNAs and DE miRNAs in the primary bovine myoblasts after RSV treatment. The mRNA results indicated that RSV treatments had high correlations with turquoise module (0.91, P-value = 0.01) and blue module (0.93, P-value < 0.01), while only turquoise module (0.96, P-value < 0.01) was highly correlated with the treatment status using miRNA data. After biological enrichment analysis, the 2579 DE genes in the turquoise module were significantly enriched in the Gene Ontology (GO) terms and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. The top two GO terms were actin filament-based process (GO:0030029) and actin cytoskeleton organization (GO:0030036). The top two KEGG pathways were regulation of actin cytoskeleton (bta04810) and tight junction (bta04530). Then, we constructed the DE mRNA co-expression and DE miRNA co-expression networks in the turquoise module, and the mRNA-miRNA targeting networks based on their co-expressions in the key module. In summary, the RSV induced miRNAs participated in the co-expression networks that could affect mRNA expressions to regulate the primary myoblast differentiation. Our study provided a better understanding of the roles of RSV in inducing miRNA and of the characteristics of DE miRNAs in the key co-expressed module in regulation of mRNAs, and revealed the new candidate regulatory miRNAs and genes for the beef quality traits.